Blending Languages: Code-Switching and Code-Mixing in Academic Arabic Communication in Abu Dhabi - Firdaus, Rifqi Muhammad; Rohanda, Rohanda; Muslikah, Siti (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This research is motivated by the multilingual proficiency of Mohamed Bin Zayed University for Humanities (MBZUH) students in Abu Dhabi. The aim of this study is to identify the forms of code-switching and code-mixing and to understand the reasons behind their occurrence in the speech of MBZUH students. The method used is descriptive research with a qualitative approach. Data analysis is conducted using the padan method and the SPEAKING method. The data sources for this study are local and international students at MBZUH, while the data itself consists of student utterances or conversations. The data collection techniques used involve two methods: the (simak) method with the (simak libat cakap) technique and the (cakap) method with the (pancing) and (cakap semuka) techniques. The results of this study identified two types of code-switching: internal and external, as well as two types of code-mixing: internal and external. Additionally, the study found three factors influencing code-switching and four factors influencing code-mixing in the speech of MBZUH students in Abu Dhabi.